Extending the European Union Waste Hierarchy to Guide Nutrient-Effective Urban Sanitation toward Global Food Security—Opportunities for Phosphorus Recovery - Drangert, Jan-Olof; Tonderski, Karin; McConville, Jennifer (Frontiers in Sustainable Food Systems, 2018)
With growing urbanization cities become hotspots for nutrients. Food items are imported and food residues, including excreta and not-eaten food, are often exported to landfill sites and water bodies. However, urban sanitation systems can be designed to achieve a high degree of nutrient recovery and food security while counteracting current nutrient resources depletion, environmental degradation and wasteful energy use. This article illustrates how an extended solid waste hierarchy also including human excreta and wastewater can guide actions to save and recover phosphorus (P) by the three sectors: food industry, households, and waste utilities. P use in diets and agricultural production is not part of the analysis, despite the potential to save P. Novel systems thinking and material flow analysis show that waste prevention can replace over 40 % of mined P presently used for making fertilisers. Reuse and recycling of P in excreta and food waste can replace another 15 – 30%, depending on P-efficiency from mine to plate. Keeping excreta separated from other wastewater facilitates such measure. Incineration and land filling are deemed the least appropriate measures since mainly P is recovered in the ashes. The European Union waste management policy is analysed for real barriers and opportunities for this approach. The EU Parliament policy guidelines were watered down in the EU Commission’s Directives and today most bio waste is still being landfilled or incinerated instead of recovered. An anticipated overcapacity of incineration plants in Europe threatens to attract all combustible material and therefore, irrevocably, reduce nutrient recovery. On the other hand, reduced generation and enhanced recovery can delay exhaustion of P resources by several centuries and, simultaneously reduce environmental degradation.